Intelligent Tuning Control of two Link Flexible Manipulator with Piezoelectric Actuator - Abdulazeem Ali, Marwah; Abdul Hussein Ali, Ahmed (Al-Khwarizmi Engineering Journal, 2022)
This paper represents an experimental study on the application of smart control represented by the use of the fuzzy logic controller. Two-link flexible manipulators that are used in airspace and military applications are made of flexible materials characterized by low frequency and damping ratio. To solve this problem, this paper proposes the use of smart materials (piezoelectric transducers), where each link is bonded with a pair of piezoelectric transducers that act as a sensor and another as an actuator. As the arm vibrates because of the movement generated by the motor, this voltage is controlled by a regulator inside the LABVIEW® 2020 software and sends the output control voltage to the piezoelectric actuator. Experimental results show that fuzzy logic control was efficient during high amplitude and led to pronounced results in suppressing vibrations within a short time. Fuzzy logic gives more flexibility to the designer and allows him to control the system through its simple implementation. This differs from classical control, which requires a mathematical model.